2018
DOI: 10.1002/ajpa.23725
|View full text |Cite
|
Sign up to set email alerts
|

Complex variation of trabecular bone structure in the proximal humerus and femur of five modern human populations

Abstract: This is the author manuscript accepted for publication and has undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
1
7

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 74 publications
(163 reference statements)
0
30
1
7
Order By: Relevance
“…The mean humeral head DA among mustelids is fairly similar to that of xenarthrans and hence greater than that commonly featured by primates [25]. However, BV/TV is lower for this VOI in mustelids than in xenarthrans, falling in the range of primates ([31,40,41,46,5557]; table 4) which might emphasize the particularly high bone content already signalled for xenarthrans in general [7073].…”
Section: Discussionmentioning
confidence: 83%
“…The mean humeral head DA among mustelids is fairly similar to that of xenarthrans and hence greater than that commonly featured by primates [25]. However, BV/TV is lower for this VOI in mustelids than in xenarthrans, falling in the range of primates ([31,40,41,46,5557]; table 4) which might emphasize the particularly high bone content already signalled for xenarthrans in general [7073].…”
Section: Discussionmentioning
confidence: 83%
“…Previous work has shown that there is substantial variation in trabecular properties within populations (Doershuk et al ; Saers et al ). Variation in bone mineral density within populations has been detected from the first year of life onwards in longitudinal studies (Loro et al ; Seeman, ).…”
Section: Discussionmentioning
confidence: 99%
“…Endurance runners were the only group in which adjusted mean TrabA differed significantly relative any other group. This enhanced distal tibial TrabA may be reflecting more complex three‐dimensional trabecular change, perhaps changes in the thickness of trabecular struts in response to loading (Doershuk et al, ; Mittra et al, ; Saers et al, ). For example, mean trabecular thickness in the calcanei of male endurance runners is significantly positively related to their weekly running distance and years of running (Best et al, ).…”
Section: Discussionmentioning
confidence: 99%